PEMILIHAN METODE PEMBONGKARAN GEDUNG BERTINGKAT MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS - Mardiaman; Fernando Simarmata (UKI Press, 2021)
The demolition is the final stage in assets life cycle. The demolished building is after reaching its life span, where the age is different for each type of building and the country where the building is located. This study focuses on the demolition of the IFC high-rise building in Jakarta. There are 4 commonly applied demolition methods: manual methods, manual with machines, mechanical, and explosives. Each method has positive and negative impacts. The purpose of this research was to choose the best method. The selection uses a hierarchical process analytical method—a list of criteria. Sub-criteria and alternatives were obtained from various sources of literature and experience. 4 elected experts filling out questions regarding criteria, sub-criteria, and alternatives were carried out in building demolition and carried out face-to-face. There are 4 criteria, 12 sub-criteria, and 4 alternatives used in the question. Based on the processing of the collected data using the hierarchical analysis of the process, the best disassembly method was obtained, respectively, the manual method with the machine (0.3435). mechanical (0.2397), manual (0.2117) and explosive (0.2052).